Application of Chitosan-Based Hydrogel Obtained from Insects in Pine Planting - Zhatkanbayev, Yerlan; Zhatkanbayeva, Zhanna; Iskakova, Zhanar; Kolpek, Ainagul; Serikov, Almas; Moldagulova, Nazira; Danlybayeva, Gaziza; Sarsenova, Ainur; Anuarbekova, Sandugash (International Journal of Biomaterials, 2023)
Agrogels, a hydrogel applied in the soil that collects water during irrigation or rainfall and distributes moisture to plant roots during drought, are a solution to water shortage concerns. Extending the release of low molecular weight chemicals has the potential to minimise mineral fertiliser losses as well as water and soil pollution. Thus, the aim of the research is to obtain chitosan from insect chitin, to synthesize a hydrogel based on chitosan with included mineral and organic fertilisers, and to report on experiments with agrogels in the field. In this study, chitosan was obtained from the adult beetles Zophobas morio. IR spectroscopy was used to examine chitosan. The existence of absorption lines typical of primary amines was demonstrated. In one step, a technique for the manufacture of chitosan-based hydrogels containing embedded mineral fertilisers was established. Hydrogel has a swelling coefficient of 60 g/g. Agrogels were evaluated while planting spruce seedlings on “Semei Ormany” LLP experimental locations. The survival rate of seedlings was found to be 40% higher in the experimental group than in the control group.